2016
DOI: 10.1158/0008-5472.can-15-1497
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Secretion of Progastrin Promotes the Survival and Self-Renewal of Colon Cancer Stem–like Cells

Abstract: Subpopulations of cancer stem-like cells (CSC) are thought to drive tumor progression and posttreatment recurrence in multiple solid tumors. However, the mechanisms that maintain stable proportions of self-renewing CSC within heterogeneous tumors under homeostatic conditions remain poorly understood. Progastrin is a secreted peptide that exhibits tumorforming potential in colorectal cancer, where it regulates pathways known to modulate colon CSC behaviors. In this study, we investigated the role of progastrin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 54 publications
4
41
0
Order By: Relevance
“…ANOVA was used for comparisons among three groups of quantitative variables, and pairwise comparisons were carried out using the Tukey post hoc test as indicated. Statistical significance of stem cell frequencies quantified using Extreme Limiting Dilution Analysis (ELDA) was assessed using the x 2 test, as described previously (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANOVA was used for comparisons among three groups of quantitative variables, and pairwise comparisons were carried out using the Tukey post hoc test as indicated. Statistical significance of stem cell frequencies quantified using Extreme Limiting Dilution Analysis (ELDA) was assessed using the x 2 test, as described previously (18).…”
Section: Discussionmentioning
confidence: 99%
“…To establish whether this is reflected by an increased self-renewal frequency of ALDH High cells, we FACSpurified ALDH High T84 cells and transfected them in suspension with claudin-2-selective or control siRNA. 12 hours later these cells were seeded in an ELDA assay and the stem cell frequency of each cell population was quantified after 10 days as described previously (18). Claudin-2 downregulation significantly decreased the stem cell frequency from 1 in every 6.24 cells (confidence interval 1/3.31-1/11.8) to 1 in every 39.8 cells (1/21.2-1/74.8; x 2 test (x 2 ¼ 14.6; Ã , P ¼ 0.000132; Fig.…”
Section: Claudin-2 Regulates the Self-renewal Capacity Of Aldh High Cmentioning
confidence: 99%
“…Initially believed to be biologically inactive, hPG80 was shown to participate in some features of a tumor, such as the disruption of cellÀcell junctions [6], cell proliferation [7], inhibition of apoptosis [8], regulation of cancer stem cells [9], and angiogenesis [10]. In addition, our team demonstrated that targeting hPG80 with a specific antibody promotes apoptosis, decreases proliferation and migration/ invasion of human colorectal cancer cells, and inhibits self-renewal of colon cancer stem cells (CSC), as well as Wnt-driven tumorigenesis in mice [5].…”
Section: Introductionmentioning
confidence: 99%
“…Novel roles of gastrins, including progastrin, are currently under discussion (Giraud et al. ; Rehfeld ). This study suggests that N‐terminal progastrin fragments infused in high doses can acutely inhibit gastrin‐stimulated acid secretion in man.…”
Section: Discussionmentioning
confidence: 99%